Labour Immigration and Union Strength - Henning Finseraas; Marianne Roed; Pal Schone (Institute of Labor Economics (IZA), 2018)
To what extent is labour mobility in the European Union a threat to the strength of unions? We argue that the combination of cheap labour, workforce heterogeneity, and low unionization among labour immigrants' is a potential challenge for unions. The challenge will be particularly severe if immigrant competition affects natives' propensity to unionize. We examine this claim using Norwegian administrative data in a natural experiment framework. The 2004 EU expansion led to a rapid increase in labour migration to the construction sector. Licensing demands, however, protected some workers from immigrant competition. Comparisons of protected and exposed workers reveal negative labour market effects of the EU expansion for exposed workers, but no effect on union membership. Our results question important theories of unionization and are relevant for research on immigration, political behaviour and collective action.
Keywords: J21; J31; J51; J61; 330; immigration; union; wages; employment